SURVEY THE PERCEPTION OF RADIATION EFFECTS AMONG MEDICAL PRACTITIONERS IN SOUTH INDIA - NOYAL MATHEW; SURESH SUKUMAR; RAJAGOPAL KV; SABU KM (International Journal of Pharma and Bio Sciences, 2016)
The present study aimed to survey the perception of radiation effects among medical practitioners in South India. A questionnaire comprising 41 multiple choice questions was given to medical practitioners belonging to different specializations in three different states of India (Karnataka, Tamil Nadu and Kerala). A response rate of 79% was obtained (300 out of 378). The mean score was 106 out of 164. It was found that only16.7% (50 out of 300) of the medical practitioners had high awareness about radiation, its associated risks and other aspects whereas 75.3 % (226 out of 300) had moderate awareness and 8 % (24 out of 300) had poor awareness. Based on specializations cardiologists, neurologists and oncologists scored better than the others. When it came to awareness based on years of experience practitioners with 1-6 years of experience were found to be more aware than their senior counterparts. It was also undermined that junior residents, assistant professors and registrars had poor awareness among other categories when awareness was associated with the designation. In all, the state of Kerala was found to have more aware practitioners than Karnataka and Tamilnadu (with 78% moderate awareness and 22% high awareness).The overall perception of radiation and its effect happens to be moderate based on the results. Therefore, it was suggested that it is best if the medical practitioners are highly aware about radiation, dose, its risks, protection and justification, considering its hazard as a carcinogenic entity.